Learning about the world from Taiwan's diplomatic allies: an exploratory practice approach. Issue 3 (26th May 2020) - Chen, Cheryl Wei-yu
ABSTRACT: This study investigates the affordances of Exploratory Practice to engage the teacher and students in dialogically researching cultures and intercultural issues in a language classroom. Aiming to engage students in learning about the world from Taiwan's diplomatic allies, the central classroom puzzle involved whether such engagement facilitated students' development of intercultural competence. The instructional procedures consisted of four stages: Setting the stage, Establishing a common ground, Joint construction, and Continuous learning . Stage-by-stage analysis revealed that students were able to take the role of co-researchers in the learning process and engage in learning about the customs and values of other countries. A sense of global citizenship was also developed in which students felt they were responsible for making this world a better place. This study ends by calling for more practitioner research like Exploratory Practice to encourage more dialogues between teachers and students.